Antioxidant activity and immunological of flavonoids isolated from leaves of Smallanthus sonchifolius (yacon) - Aguilar F., Enrique (2009)
This work was carried out with the purpose to isolate and structural chemistry elucidate the flavonoids of the leaf from the Smallanthus sonchifolius and to determine his antioxidant and immunological activity in mice Balb/C. The samples were collected in the department of Ayacucho and were extracted with ethanol 80%, while that fats, waxes, and chlorophyll removed with petroleum ether, the aqueous layer was extracted with ethyl acetate. The flavonoids were isolated from the ethyl acetate extract for thin layer chromatography preparative, using the solvents system BAW (4:1:5) and visualized with ultraviolet light at 366 nm. The flavonoids structure was elucidated by ultraviolet spectroscopic, using the Mabry et al tables. It was determined the bioassays utilizing brine shrimp (Artemia salina) and the acute oral toxicity for the doses limit test in mice. The antioxidant activity was evaluated for DPPH scavenger, inhibition the liberation de hydroxyl radical and lipid peroxidation in hepatic microsomal. The immunological activity was evaluated experimentaly in inmmunosupressed mice with cyclophosphamide. It was obtained 1% yielding of flavonic fraction. The flavonoids isolated were: 5, 7-dihydroxy-4’-methoxyflavonol, 5, 7, 3’-trihydroxy-4’-methoxyflavonol, 5-hydroxy-4’-methoxy-7-O-glycosilflavone and 7,4’-dihydroxy-3,5’-dimethoxyflavone, that to demonstrate have antioxidant activity similarly to rutin, quercetin and vitamin C, concentration dependent (p<0.05) and the immunological activity, stimulating the increase the number of the both white blood and red blood cells in inmunosupressed mice and without evidence significant toxicity. It was conclude that the flavonoids in leaf of Smallanthus sonchifolius have antioxidant and immunological activity and any evidence of toxicity at.